Design and control of a DC-DC converter - Kok, Safacan (Nanyang Technological University, 2024)
This project presents the design and control of a DC-DC converter, focusing on developing an educational gadget used for teaching purposes in class EE4207 Control Engineering and Desing module. A comparison between two methods of control, analogue and digital, implemented on a buck converter will be examined.